Uncertainty shocks, equity financing, and business cycle amplifications - Park, Jongho (Journal of Corporate Finance, 2024)
We develop a computable general equilibrium model of firm capital structure that predicts countercyclical financing costs and procyclical financing. We extend the standard financial accelerator model by incorporating countercyclical uncertainty shocks and equity financing frictions capturing the moral hazard problem of profit diversion. In this environment, increased uncertainty restricts equity financing, resulting in a lower level of total equity, which in turn influences the debt contract. As a result of less equity utilization in the face of increased uncertainty, the default rate and debt financing costs increase, although firms reduce their investments. The amplified effect of uncertainty shocks on debt financing costs through the equity financing channel enables the model to predict countercyclical external financing costs. Existing financial accelerator models, on the other hand, cannot generate countercyclical financing costs without uncertainty amplification via equity financing, as TFP shocks, another source of business cycle, cause firms to reduce the size of business projects and, in turn, credit demand.